Changing the climate risk trajectory for coral reefs - Condie, Scott A. (Frontiers in Climate, 2022)
Coral reefs are extremely vulnerable to climate change and their recent degradation will continue unless we can instigate strong global climate action with effective local interventions. Many types of intervention have been proposed and some aspects of their deployment are now being tested. However, their long-term efficacy under climate change can only be evaluated using complex ecological models. The associated uncertainties in climate trajectories, ecological responses, and the mitigating effects of interventions, necessitate the use of a risk-based approach to evaluating model results. We show that ensemble modelling can be used to develop rigorous risk assessments suitable for comparing intervention strategies. A major strength of this approach is that all the key elements required for risk assessment (exposure, sensitivity, adaptive capacity and impacts) can be generated by the model in a dynamically consistent form. This is a major advance on semi-quantitative climate change vulnerability risk assessments that estimate these quantities independently and then combine them under additional assumptions. Applying ensemble modelling risk assessment to the Great Barrier Reef suggests that regional intervention strategies, such as solar radiation management and control of coral predators, can slow the increase in risk and potentially avoid extreme risks predicted for the second half of the century. Model results further suggest that deployments focused within the central GBR will be most effective due to underlying patterns of reef connectivity.